Heterogeneous labour demand in the Colombian manufacturing sector - Luis-Esteban Álvarez; Francesca Castellani; Nataly Obando (Journal for Labour Market Research, 2019)
Using the Colombian Annual Manufacturing Survey between 2000 and 2013, we investigate the heterogeneity in labour demand within the industrial sector based on the elasticities. We find that long-run own-price, output, and TFP elasticities vary across a variety of dimensions such as regions, sectors, and plant sizes depending on workers' skills and contract modalities (open-ended and temporary). The determinants of industrial labour demand are quantitatively different, mainly, across regions and, to some extent, subsectors when we focus on demand for unskilled workers. It is possible that, given the importance of apparel in the manufacturing sector in Pereira, labour demand for permanent skilled workers in that city is different from that of Bogotá, Cali, and Medellín. Thus, labour demand heterogeneity is just a symptom of the underlying differences in the production processes and produced goods, technologies, labour force qualification and productivity, preferences of workers, rigidities and wage-setting procedures, and peculiarities of goods' markets, etc. Suggestions to induce more wage flexibility and decrease labour segmentation emerge from this paper.
Keywords: J23; R32; 330; Regional disparities; Skilled and unskilled workers; Temporary and open-ended contracts; Labour segmentation